Experiences of distress and gaps in government safety net supports among parents of young children during the COVID-19 pandemic: a qualitative study - Alyssa C. Mooney; Kaitlyn E. Jackson; Rita Hamad; Lia C. H. Fernald; Mekhala Hoskote; Wendi Gosliner (BMC, 2023)
Abstract Background The COVID-19 pandemic prompted rapid federal, state, and local government policymaking to buffer families from the health and economic harms of the pandemic. However, there has been little attention to families' perceptions of whether the pandemic safety net policy response was adequate, and what is needed to alleviate lasting effects on family well-being. This study examines the experiences and challenges of families with low incomes caring for young children during the pandemic. Methods Semi-structured qualitative interviews conducted from August 2020 to January 2021 with 34 parents of young children in California were analyzed using thematic analysis. Results We identified three key themes related to parents' experiences during the pandemic: (1) positive experiences with government support programs, (2) challenging experiences with government support programs, and (3) distress resulting from insufficient support for childcare disruptions. Participants reported that program expansions helped alleviate food insecurity, and those attending community colleges reported accessing a range of supports through supportive counselors. However, many reported gaps in support for childcare and distance learning, pre-existing housing instability, and parenting stressors. With insufficient supports, additional childcare and education workloads resulted in stress and exhaustion, guilt about competing demands, and stagnation of longer-term goals for economic and educational advancement. Conclusions Families of young children, already facing housing and economic insecurity prior to the pandemic, experienced parental burnout. To support family well-being, participants endorsed policies to remove housing barriers, and expand childcare options to mitigate job loss and competing demands on parents. Policy responses that either alleviate stressors or bolster supports have the potential to prevent distress catalyzed by future disasters or the more common destabilizing experiences of economic insecurity.